2019
DOI: 10.3390/ijerph16020221
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Lean Construction on Safety Systems: A System Dynamics Approach

Abstract: Lean construction has been viewed as an effective management approach for reducing the occurrence of no-value or destructive activities, such as wasting resources and safety-related accidents. However, few studies have systematically addressed how and to what extent lean construction practices influence construction safety. To bridge this gap, a conceptual model is developed and validated using a system dynamics approach. The construction system in this model comprises four sub-systems (i.e., environment syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
1
16
0
9
Order By: Relevance
“…This result emphasizes the importance of workplace management in encouraging construction safety. This finding is in line with that of Wu et al [64], who found that an effective safety system for reducing the occurrence of construction accidents should include safety planning of environment and equipment. In practice, construction practitioners should pay attention to the provision of good work conditions for construction workers to work safely.…”
Section: Discussionsupporting
confidence: 92%
“…This result emphasizes the importance of workplace management in encouraging construction safety. This finding is in line with that of Wu et al [64], who found that an effective safety system for reducing the occurrence of construction accidents should include safety planning of environment and equipment. In practice, construction practitioners should pay attention to the provision of good work conditions for construction workers to work safely.…”
Section: Discussionsupporting
confidence: 92%
“…The latest research found that new construction equipment (such as GPS and physiological sensors) can improve the management level of occupational safety and health (39). Through the use of modern support technology, lean construction, safe construction, and management can be achieved (40)(41)(42). The world has paid great attention to OHS in the era of industry 4.0, which will bring about a new paradigm shift, which will have a profound impact on OHS management (43).…”
Section: Introductionmentioning
confidence: 99%
“…The data related to the GCC construction industry, safety and health in construction particularly in the GCC region and methods to improve the safety performance in construction were collected using systematic literature review. A similar approach was also adopted by Wu et al, (2019) in their study related to the impacts of lean construction on safety systems. Different databases including Web of Science, Scopus, Proquest and Science Direct were used for the systematic review.…”
Section: Methodsmentioning
confidence: 99%